Pengaruh Pengungkapan Islamic Social Reporting (ISR) Dan Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan Pada Bank Umum Syariah Perbankan Indonesia - Fitri Anggriani; Abrar Amri; Syafrizal Syafrizal (CV. ITTC INDONESIA, 2025)
This study examines the effect of Islamic Social Reporting (ISR) and Corporate Social Responsibility (CSR) disclosure on the financial performance of Islamic Commercial Banks (BUS) for the 2021-2024 period. ISR in this study is projected through the ISR index score, CSR is projected through the CSR score index, and financial performance is projected through ROA. Data in this study were obtained from the official websites of BUS and the Financial Services Authority (OJK). The sample used was 8 BUS that published annual financial reports for the 2021-2024 period. The sampling method in this study was purposive sampling. The data analysis method used in this study was panel data regression analysis using Eviews 12 software. The results of this study indicate that ISR partially has a positive and significant effect on the financial performance of Islamic Commercial Banks. Meanwhile, CSR partially and significantly does not affect the financial performance of Islamic Commercial Banks. Simultaneously, the ISR and CSR variables do not affect the financial performance of Islamic Commercial Banks